Are new metrics pushing out traditional measurement tools of academic communications and scholarship? - Sedigheh Mohammadesmaeil; Alireza Atarodi (Gonabad University of Medical Sciences, 2015)
ntroduction: Universities are the centers of interactions and communications and a basic of scientific products and publications in the country. Scientific production and publications are surveyed and evaluated for various reasons. Evaluation criteria with regard to the location, type and circumstances are different and are occasionally changed and new. In this study, we survey the new metrics and metric tools of academic production and publications and faculty members' perspectives in this field. Method: This is a descriptive and a cross-sectional study. The overall objective of this study was "The survey of social media metrics in academic communications and faculty members of Gonabad medical university perspective on these metrics in 2015" The data were collected by a study of library and information sources and using a self-made questionnaire and then were analyzed by SPSS-16 software. Results: The Metrics and criteria for evaluation of scientific publications are in two traditional and new ones, and can also be supplemented or replaced. Most of the faculty members, ie 43 (55.8%) suggested using of both methods together to evaluate scientific publications. There was a significant relationship between knowing the metrics with gender (at 0.001), with the number of articles (at 0.002), and with career record (at 0.000) and the education field (at 0.022). The main hypothesis was approved. Conclusion: Evaluation and metric for any scientific production can enrich it and move towards a more qualitative work and will make the scientific productions more effective. The criteria and metrics would be useful and appropriate with having quantity and quality properties and to be able to evaluate properly, comprehensively, all tangible and intangible properties and create a healthy scientific competition since, the future health and well-being of a society depends on the quantity and quality of science and technology in that society.